Gastrointestinal and Hepatic Manifestation of Dengue and its Role in Prediction of Severity in Children (Faridpur Medical College Journal, 2025)
Dengue fever is a communicable disease having variable clinical manifestations. Gastrointestinal (GI) manifestations also occur in dengue. Diagnosis of the disease may be missed without proper knowledge about these presentations. This study was carried out to explore GI manifestations of dengue fever and define its role in identification of severe dengue. This cross-sectional observational study was conducted at Chattogram Medical College Hospital, Bangladesh from November, 2022 to December, 2022. After detailed history, examinations and investigations total 101 children of dengue fever were divided into two groups naming dengue fever with or without warning sign and severe dengue fever (SDF). Comparison was done in between groups in context of GI symptoms and investigations. Among total 101 patients 24 (23.76%) got SDF. Mean age was 6.83±3.9 years with a Male: Female ratio of 1.5:1. Majority (86.1%) having GI symptom. Common presentations were vomiting (69.3%), abdominal pain (59.4%), nausea (25.7%), anorexia (22.8%), diarrhea (17.8%). Other observed GI manifestations were ascites (8.91%), melena (7.92%), hematemesis (1.98%), jaundice (0.99%) hepatomegaly (1.98%), acute pancreatitis (0.99%) and acute liver failure (0.99%). Among these diarrhoea, ascites, melena were found significant with dengue severity (p=0.00). Raised S. ALT was seen in 39.6% cases which significantly corresponds with SDF (p=0.00). In conclusion, GI manifestation is very common in dengue fever and often appears as main presenting symptom associated with fever. Among various typical and atypical GI symptoms; diarrhea, ascites, melena, transaminasemia can be used as a predictor of severe dengue.Faridpur Med. Coll. J. 2025;20(1):7-12